FREQUENCY OF TETANUS TOXOID IMMUNIZATION AMONG COLLEGE/UNIVERSITY FEMALE STUDENTS OF KARACHI - Qadir, Murad; Murad, Rafat; Mumtaz, Seema; Azmi, Abdul Azim; Rehman, Rehana; Hani, Omm -E-; Aziz, Nasir (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tetanus is a deadly infectious disease for which immunisation is available in EPI at both infant level and for females of reproductive age. More than 95% of patients who develop tetanus have not been previously immunised. Objectives of the study were to determine the frequency of tetanus vaccination and to access the awareness of immunisation among females studying in 11 girls’ colleges of Karachi and University of Karachi. Method: A cross sectional study was conducted among 1,407 females studying in colleges and University of Karachi from April to August 2007 using a prescribed questionnaire. Result: Among 1,407 female students who were interviewed for the study, 232 (16.48%) were not aware about tetanus immunisation program for females of reproductive age. Only 560 students (39.80%) received at least 1 of 5 recommended doses. Only 41 female students (2.91%) received complete course of 5 doses. Conclusion: Coverage of tetanus immunisation among literate females in most populous city of the country is far behind satisfactory. There is need for awareness and crash programs of tetanus immunisation. Keywords: Tetanus, Immunisation, Vaccination, Toxoid